Will CEOs with banking experience lower default risks? Evidence from P2P lending platforms in China - GONG, Qiang (Institutional Knowledge at Singapore Management University, 2020)
Using a novel dataset of 121 Chinese P2P lending platforms, we investigate the impact of CEOs' banking experience on default risk. The empirical results indicate that CEOs with prior banking experience manage default risk better. Moreover, CEOs' banking experience has a stronger influence on small platforms and in situations where the platforms' depository banks are city commercial banks. Our results indicate that although fintech provides technology to reduce risks, we cannot ignore the constructive role of professional experience in risk management. Thus, investors and regulators in emerging markets should pay attention to managers' financial qualifications, and especially to CEOs' banking experience.